Diffuse Alveolar Hemorrhage in Systemic Lupus Erythematosus: Histopathologic Features and Clinical Correlations. (27th April 2017) - Ta, Robert; Celli, Romulo; West, A. Brian
Abstract : The case of a 16-year-old African-American girl with systemic lupus erythematosus, who developed diffuse alveolar hemorrhage with fatal consequences, is described. Diffuse alveolar hemorrhage is a rare but serious complication of systemic lupus. It occurs in three distinct but overlapping phenotypes, acute capillaritis, bland pulmonary hemorrhage, and diffuse alveolar damage, each of which is associated with a different group of underlying conditions. Diffuse alveolar hemorrhage is a medical emergency: choice of treatment depends on early diagnosis and determination of the underlying etiology. Acute infection, superimposed on diffuse alveolar hemorrhage in the setting of immune compromise, is often a terminal event, as in this case.